Critical Thinking Skills: British Parliamentary Debate System to Improve English as Foreign Language (EFL) Students’ Critical Speaking - Sri Wahyuni; Hijjatul Qamariah; Sofyan A. Gani; Yunisrina Qismullah Yusuf; Mulyadi Syahputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Debate as one of techniques in teaching speaking has been believed can accommodate and facilitate teachers in improving students speaking skill. It is also believed that students’ critical thinking can be ignited though debate technique. This research, therefore would like to employ the debate technique of British parliamentary system in teaching speaking in order to initiate students critical thinking. This is a quantitative research by applying experimental method. The population of this study was English speaking class in private Higher Education (PTS) in Aceh and the sample were two English speaking classes in Private Higher Education in Aceh. The sample, however, were two English speaking classes in Private Higher Education in Aceh. The data of this study were gained from pre test and post test, thus the results of the test were then analyzed though statistic formula. From the analyzed data, it was showed that in sample 1, the t table was 2.145 and t-test was 6.006, in sample 2 the t table was 2.228 and t-test was 2.936. The research finding revealed that, the t-test found was higher than t-table. It can be concluded that Ho in the study was rejected that there was an improvement on students’ critical thinking skill after applying the British Parliamentary debate system.